Experience of the 'Ear Glove' in children with microtia. (September 2022) - Lancer, Hannah; Hood, Kelly; Halliday, Edwin; Tzifa, Konstance; Lloyd, Mark; McDermott, Ann-Louise
Abstract: Introduction: Microtia is a congenital condition which can be found in isolation or as part of a syndrome. The key factors to consider when treating a child with microtia are hearing, speech and language development, cosmesis, and the psychological impact on the patient as well as the family. As children age and become more self-aware, the anxiety about transition from primary to secondary school can often be a trigger for carers and child to want a cosmetic solution at a younger age. Any form of cosmetic surgery ideally requires a child with an understanding of what is involved, as well as sufficient growth and anatomy to provide soft tissue resources for surgery. An additional issue for some children with microtia is the concern about adding to their already 'different' appearance by using a bone conduction solution/hearing implant. We present the outcomes of a novel non-surgical prosthesis 'Ear Glove' offered to pediatric patients with microtia. Methods: Children with microtia are seen in the multidisciplinary outpatient clinic and reviewed by the team which includes an Otolaryngologist, Audiologist, Plastic surgeon and Maxillofacial prosthetist. When discussing cosmesis, all reconstruction options are explored. These include a 'no treatment' option, both adhesive and implant-retained prosthetic ears, and autologous and/or MedporⓇ ear reconstruction (age appropriate). All children who chose to undergo the adhesive non-surgical prosthetic option 'Ear Glove' for microtia were identified by our prosthetic department (n = 9), and their outcomes reviewed. Results: Nine children have been fitted with the 'Ear Glove', with all 9 achieving excellent symmetry and aesthetics. Seven patients continue to successfully use their prostheses either daily or for special occasions. Two of these patients also decided to undergo bone anchored hearing implant surgery. One patient opted to change his treatment plans and chose 'no treatment' after feeling he preferred his 'little' ears. Finally, one patient reported the daily use of adhesive to be a deterrent. No skin reactions to the adhesive were reported in any patient. Conclusions: The 'Ear Glove' is increasingly being used by microtia patients in our department to good effect. This non-surgical alternative allows young patients to appreciate the cosmetic results of the surgical options before committing to an invasive procedure. Highlights: Hearing should be prioritized when evaluating patients with microtia. Cosmetic and psychological aspects should always be considered. No treatment, prosthetic, or surgery are suitable management options. The 'Ear Glove' is useful in decision making for children unsure about surgery. Prosthetic ears can provide early cosmetic solutions for children.